kajian macam dan dosis pupuk organik terhadap pertumbuhan ketela pohon - Annisa Witular; JM Sri Hardiatmi; Kharis Triyono (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
Study the Types and Dosage of Organic Fertilizers of Cassava (Manihot esculenta Crantz). The research to observe the development of cassava due to the influence of cassava based on organic fertilizer. This research was conducted from October 2019 to January 2020, in the Experimental Garden of the Faculty of Agriculture, Slamet Riyadi University, Surakarta. This study used a Completely Randomized Design (CRD) method with 1 treatment, namely type and dose of organic fertilizers and obtained 10 combinations treatments and each was repeated 3 times. From the research data, analysis of variance will be carried out nd then the real difference test will be countinued with the real Honestly Significant Difference test at the 5% level. In this observation observed included 8 parameters: shoot height, longest root length, number of roots, number of leaves,fresh weight of planted roots, dry weight of planted roots, fresh weight of planting buds, and dry weight of planting buds. The results showed that (1) effect of kinds and dosages of organic fertilizer the effect very apparent in the parameters of the number of planted leaves, number of planted roots, longest root length, dry weight of planted roots, fresh weight of planted shoots and dry weight of planted shoots. Significantly affected the shoot height parameters. No significant effect is found on the parameters of the fresh root weight of the crop. (2) The dosage of 1.9 kg / polybag (MD7) fertilizer application gave the best results on the dry weight of shoots, 378 grams.